PELATIHAN PENGEMASAN PUPUK ORGANIK PADAT DAN CAIR DI KELOMPOK TANI MEKAR SARI DUSUN KELOR BANGUNKERTO TURI SLEMAN - Wahyurini, Endah; Suryawati, Ami; Gumelar, Rima Margareta Retnyo; Huda, Amalia Nurul; Nabila, Nailan (Dharma: Jurnal Pengabdian Masyarakat, 2023)
Kelor Bangunkerto Turi Sleman Hamlet has become a tourist spot, the people there are a group of farmers whose highlands are planted with snake fruit and horticultural crops. Plant waste in the form of dry leaves and household waste is processed into compost and liquid organic fertilizer, in an effort to reduce the use of chemicals on plants. The main problem faced by farmers is that the quality of organic fertilizer packaging is not yet optimal, which is attractive and can last a long time. The aim of this community service is to provide training and mentoring in technical skills for packaging solid and liquid organic fertilizers that are attractive and safe so that they are suitable for sale. The method used was socialization followed by training on packaging solid and liquid organic fertilizer, training on packaging design and procurement of packaging equipment. The results of this service are increased knowledge, skills and welfare of the community, solid organic fertilizer products in plastic packaging, liquid organic fertilizer products in plastic jerry can bottles, branding logo for fertilizer produced by KT MEKAR SARI Kelor, Bangunkerto Turi Sleman DIY.